Ataques especulativos e crises cambiais: uma análise da crise brasileira de 2002 - Mira, Roberta (2006)
Since the middle of the 1990s economic research relative to speculative attacks has focused attention on developing a new generation model to predict ex ante the likelihood of a currency crisis on a specific country or region. This new family of currency crisis models was denominated Early Warning Systems, well known as EWS Models. This paper examines the 2002 Brazilian Crisis in order to answer two basic questions: a) The empirical literature analysis suggests that the extreme volatility in the Brazilian foreign exchange market on this period could be classified as currency crises? c) Which indicators, considered as one or as a group, could be related to this episode? With this purpose, this paper revisits the main topics on the theoretical literature of speculative attacks, currency crisis and EWS Models. More specifically it examines the Frankel and Rose (1996) precise definition on currency crisis duly adapted to a flexible exchange rate regimes. Also, it was elaborated a vector auto-regression model (VAR) trying to identify which indicators could be related to the extreme exchange market pressure in the 2002 domestic market